2005
DOI: 10.1007/s00134-005-2632-2
|View full text |Cite
|
Sign up to set email alerts
|

Severe traumatic brain injury in pediatric patients: treatment and outcome using an intracranial pressure targeted therapy—the Lund concept

Abstract: Objective: This study evaluated the outcome of treatment according to the Lund concept in children with severe traumatic brain injury and investigated whether the preset goals of the protocol were achieved. Design and setting: A twocenter retrospective study in neurointensive care units at university hospitals. Patients: Forty-one children with severe traumatic brain injury from blunt trauma and arriving at hospital within 24 h after injury. Median age was 8.8 years (range 3 months-14.2 years), Glasgow Coma Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 43 publications
3
36
1
Order By: Relevance
“…We have previously reported our results in adults and in children using this concept, where a mortality rate of about 10% and a favorable outcome (GOS 5 and 4) in approximately 70% of the patients treated was demonstrated (Naredi et al, 2001;Wahlstrom et al, 2005). In the present study, these results were confirmed in patients with DC as an additional step in the TBI treatment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We have previously reported our results in adults and in children using this concept, where a mortality rate of about 10% and a favorable outcome (GOS 5 and 4) in approximately 70% of the patients treated was demonstrated (Naredi et al, 2001;Wahlstrom et al, 2005). In the present study, these results were confirmed in patients with DC as an additional step in the TBI treatment.…”
Section: Discussionsupporting
confidence: 82%
“…This treatment concept was introduced in our clinical practice in 1994. Four outcome studies published from three different university hospitals in Sweden using the protocol have shown a mortality rate of about 10% and favorable outcomes as indicated by Glasgow Outcome Scale (GOS) 4-5 in 70% of the patients suffering from severe TBI (Eker et al, 1998;Naredi et al, 1998Naredi et al, , 2001Wahlstrom et al, 2005). In 1997, we introduced the use of decompressive hemi-craniectomy as an additional step in our protocol-guided treatment of TBI.…”
Section: Introduction Smentioning
confidence: 99%
“…That the study group so defined was "severe" is supported by the overall mortality rate of 24%, which is comparable to mortality rates for severe TBI among children defined by GCS or AIS scores in contemporary case series and prospective trials. 2,9,11,17,24,25,34,35,39,40,43,44,46,47 Nevertheless, the rate of neurosurgical procedures in the current study group (46.8%) was unexpectedly low. Even among admissions lasting 2 days or longer and ending in death, the rate of neurosurgical procedures was only 67.3%.…”
Section: The Missing Icp Monitorscontrasting
confidence: 51%
“…The median time between accident and arrival in our hospital is ~ 8 hours. 21,38 This is due to the size of our catchment area, 1000 km to the north, 600 km to the south, and 400 km to the west. Therefore, it is impossible for us to initiate EEG monitoring as early as Vespa et al 37 reported, but we are able to start well within the time frame reported by Ronne-Engström and Winkler.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously published our outcome results, [20][21][22]38 which showed a favorable outcome in the range of 70% and a mortality of < 15%. One factor contributing to the good outcome could be that we have a low frequency of or no EEG seizures.…”
Section: Discussionmentioning
confidence: 99%